4. MEMAHAMI TAYANGAN KEKERASAN DI TELEVISI - Suprihatini, Taufik (Faculty of Social and Political Sciences Diponegoro University, 2008)
Nowdays, crime has been part of daily life in Indonesian people. It is easy for us to find the news of criminal in newspaper, tabloid, magazine, television and other mass media, moreover, it is often become main topic even in infotainment. In other word violence is adhere to Indonesian people’s life, because it is not only appear in great moment like transition of power but also in daily live. We often watch in television when someone is not guilty but he has to lose his life. He has been attacked overwhelwirsly and beat just because people shout to him as a thief. Nevertheless, when we observe, the arresting process or reaction of a victim are incident that have been exposed frequently, so the effect of violence show give negative attitude for the public of media. As a nation that admit, hold in respect and bent on uphold to the Human Right, all violence have been proceed according to the law in order to accomplish justice and protect people’s rights including the victim and suspect.